Targeting non-pulmonary vein triggers in persistent atrial fibrillation: results from a prospective, multicentre, observational registry. Issue 12 (21st August 2021) - Della Rocca, Domenico G; Di Biase, Luigi; Mohanty, Sanghamitra; Trivedi, Chintan; Gianni, Carola; Romero, Jorge; Tarantino, Nicola; Magnocavallo, Michele; Bassiouny, Mohamed; Natale, Veronica N; Mayedo, Angel Quintero; Macdonald, Bryan; et al.
Abstract: Aims: We evaluated the efficacy of an ablation strategy empirically targeting pulmonary veins (PVs) and posterior wall (PW) and the prevalence and clinical impact of extrapulmonary trigger inducibility and ablation in a large cohort of patients with persistent atrial fibrillation (PerAF). Methods and Results: A total of 1803 PerAF patients were prospectively enrolled. All patients underwent pulmonary vein antrum isolation (PVAI) extended to the entire PW. A standardized protocol was performed to confirm persistent PVAI and elicit any triggers originating from non-PV sites. All non-PV triggers initiating sustained atrial tachyarrhythmias were ablated. Ablation of non-PV sites triggering non-sustained runs (<30 s) of atrial tachyarrhythmias or promoting frequent premature atrial complexes (≥10/min) was left to operator's discretion. Overall, 1319 (73.2%) patients had documented triggers from non-PV areas. After 17.4 ± 8.5 months of follow-up, the cumulative freedom from atrial tachyarrhythmias among patients without inducible non-PV triggers ( n  = 484) was 70.2%. Patients with ablation of induced non-PV triggers had a significantly higher arrhythmia control than those whose triggers were not ablated (67.9% vs. 39.4%, respectively; P  < 0.001). After adjusting for clinically relevant variables, patients in whom non-PV triggers were documented but not ablated had an increased risk of arrhythmia relapse (hazard ratio: 2.39; 95% confidence interval: 2.01–2.83; P  < 0.001). Conclusion: Pulmonary vein antrum isolation extended to the entire PW might provide acceptable long-term arrhythmia-free survival in PerAF patients without inducible non-PV triggers. In our population of PerAF patients, non-PV triggers could be elicited in ∼70% of PerAF patients and their elimination significantly improved outcomes.